2022
DOI: 10.1007/s00592-022-01914-y
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus and cardio-metabolic risk factors in women and children at 3 years postpartum

Abstract: Introduction Gestational diabetes mellitus (GDM) is thought to be associated with cardio-metabolic risk factor development in women and their children during the early postpartum period and early childhood. We hypothesized that these women and their children would exhibit increased abnormal cardio-metabolic risk factors three years after pregnancy. Methods Women from the Screening Tests to Predict Poor Outcomes of Pregnancy study were invited to attend a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Upregulation of placental inflammatory cytokines, oxidative stress-related genetic variants (myeloperoxidase G-463 A, CYBA C242T, CYP2E1 C-1054T, etc. ), glycation and oxidation of proteins caused by hyperglycemia were associated with unfavourable metabolic profiles, insulin resistance, increased oxidative stress, and state of chronic inflammation in patients with GDM, which might increase the risk of adverse perinatal outcomes [ 6 , 8 , 11 , 20 , 21 , 47 ]. In contrast with most of published data in literature [ 2 , 6 , 21 ], in the present study, we found that the gestational weight gain and the birth height and weight of neonates were lower, whereas the incidence of macrosomia were similar in the GDM group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of placental inflammatory cytokines, oxidative stress-related genetic variants (myeloperoxidase G-463 A, CYBA C242T, CYP2E1 C-1054T, etc. ), glycation and oxidation of proteins caused by hyperglycemia were associated with unfavourable metabolic profiles, insulin resistance, increased oxidative stress, and state of chronic inflammation in patients with GDM, which might increase the risk of adverse perinatal outcomes [ 6 , 8 , 11 , 20 , 21 , 47 ]. In contrast with most of published data in literature [ 2 , 6 , 21 ], in the present study, we found that the gestational weight gain and the birth height and weight of neonates were lower, whereas the incidence of macrosomia were similar in the GDM group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the women who participated in our follow-up may have had cardio-metabolic risk factors pre-pregnancy. Of the women who attended the 3 year follow-up, 22% of these women had metabolic syndrome in pregnancy [ 44 ]. However, it is likely that assessing covariates from early pregnancy such as BMI, smoking status and SEI likely also reflect pre-pregnancy status and this could be accounted for in part [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably the first trial utilizing multi-sectoral inventive biomarkers to assess the risk of cardiometabolic disease in women with pregestational diabetes. On this account, women with pGDM could be incorporated into follow-up programs tailored to guarantee consistent supervision, thus delivering efficient prevention of both cardiovascular disease and type 2 diabetes (DM2) [ 49 ].…”
Section: Pregnancy Complicationsmentioning
confidence: 99%